Factors Affecting the Decision to Become a Parent: A Content Analysis - Fahimeh Ranjbar; Farideh Khalajabadi Farahani; Simin Montazeri; Mina Taheri; Mojgan Mirghafourvand; Tahereh Sadeghi; Parvaneh Darabi; Maryam Gharacheh (Health Science Reports, 2025)
ABSTRACT Background and Aims The persistent issue of low fertility rates in many countries, including Iran, has raised concerns regarding population decline, aging demographics, and increasing dependency ratios. This situation underscores the necessity of investigating the factors that contribute to these trends and the implementation of policies to encourage childbearing. This study aims to explore the underlying factors related to childbearing intentions among young Iranian men and women who are about to be married. Methods This study analyzed responses from participants in premarital courses to the survey question, “What circumstances may affect your decision to become a mother or father?” The main survey was conducted between June 22, 2021 and March 16, 2022, involving 1533 women and 1405 men who were about to marry and attended premarital courses at public health clinics across 5 cities in Iran. Data were collected through web‐based questionnaires. The responses to this open question were text‐based and sufficiently detailed for content analysis. A total of 334 text‐based responses were analyzed using MAXQDA version 11, resulting in 270 open codes that were categorized based on thematic concepts. Results The main categories that emerged from the analysis were “Obscure Prospects” and “Individual Life Goals, Preferences, and Concerns.” The “Obscure Prospects” category included 181 codes, highlighting concerns related to economic hardship and sociopolitical conditions. In contrast, the “Individual Life Goals, Preferences, and Concerns” category comprised 89 open codes, focusing on disinterest in having children and the intention to postpone childbearing for various personal reasons. Conclusion The results indicate that factors such as the role of an uncertain future arising from economic, social, and cultural challenges on fertility decisions, along with delays in childbearing due to prioritizing personal development goals, are critical considerations that must be addressed to ensure the success of new pronatalist policies in Iran.